Framework Design IoT for Smart Agriculture - Dewi Indri (APIC, 2021)
West Bandung Regency has a very abundant potential of natural resources, one of which is in agriculture. Agriculture is the use of resources made by humans to produce food and manage their environment. One of problem is the inability of farmers to supervise and take care of crops so that an intelligent agricultural system based on IOT is required. The intelligent agricultural system aims to predict and monitor the problems faced by farmers to increase the productivity of agricultural products. In this study, it proposed a design of intelligent agricultural framework by configuring several sensors that generated data from agricultural land and then the information is presented in the monitoring system for the use of the user to determine the decisions in conducting agricultural activities.